Peningkatan Pengetahuan Literasi Sains Siswa Sekolah Dasar Melalui Penerapan Model Problem Based Learning pada Materi Siaga Bencana Gempa Bumi - Maghfira Izzania, Rizqa Dwi Shofiya; Winarni, Endang Widi; Ramadhani, Muhammad Habib; Agusdianita, Neza (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the effectiveness of the Problem-Based Learning (PBL) model in improving elementary school students’ science literacy knowledge on the topic of earthquake disaster preparedness. The research employed a quasi-experimental method with a matching only pretest-posttest control group design. The population consisted of fourth-grade students from SD Negeri 04, SD Negeri 08, and SD Negeri 11 in Bengkulu City. Samples were selected using a cluster random sampling technique, resulting in class IVB of SDN 08 as the experimental group and class IVA of SDN 11 as the control group. Data were collected using a science literacy test covering three knowledge aspects: content, procedural, and epistemic. Data analysis was conducted using an independent sample t-test, gain score calculation, and effect size (Cohen’s d), assisted by SPSS version 29. The analysis results revealed a significant difference in learning outcomes between the experimental and control groups. The high gain score and effect size value (Cohen’s d = 1.27) indicate that the PBL model is highly effective in enhancing students’ science literacy knowledge. The implementation of this model has been proven to strengthen conceptual understanding, scientific skills, and epistemic awareness, which are essential for disaster preparedness. Therefore, the PBL model is recommended as a relevant and contextual learning approach for elementary education.